IPM - still a gap between theory and practice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Bad Durkheim, Germany in February 1989 conference on integrated pest management (IPM) in tropical and subtropical regions